PENGARUH HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA CACAPA SDN PLUMBUNGAN - Diana Rizki, Mifta; Purbasari, Imaniar; Ari Pratiwi, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A study conducted at SDN Plumbungan focused on improving elementary school students' learning outcomes in Pancasila Education by implementing the Problem-Based Learning model assisted by cacapa media (canva cartoon Pancasila). The research aimed to address issues including lack of student interest, low classroom engagement, monotonous lectures, and limited learning media. The research followed a quantitative experimental model, using a one-group pretest posttest design with a sample size of 25 students. Various data collection techniques were employed, such as tests, interviews, observations, and documentation. The findings revealed a significant improvement in student learning outcomes, with an average pretest score of 48.2 and an average posttest score of 77. The hypothesis testing confirmed the impact of the Problem-Based Learning model assisted by cacapa media, as indicated by a significance value (2-tailed) of 0.000, confirming that Ha is accepted and Ho is rejected. Thus, the study demonstrated that the application of this learning model positively influenced Pancasila Education in the fourth-grade class at SDN Plumbungan.